Mid-Infrared Spectroscopic Study of Cultivating Medicinal Fungi Ganoderma: Composition, Development, and Strain Variability of Basidiocarps - Synytsya, Andriy; Bleha, Roman; Skrynnikova, Anastasia; Babayeva, Tamilla; Čopíková, Jana; Kvasnička, František; Jablonsky, Ivan; Klouček, Pavel (Journal of fungi (Basel, Switzerland), 2023)
Attenuated total reflection Fourier-transform infrared (ATR-FTIR) spectroscopy was proposed for rapid, versatile, and non-invasive screening of Ganoderma basidiocarps to assess their potential for specific applications. Fifteen species and strains of this fungus were selected for analysis, and fine sections at different parts of young and mature basidiocarps were obtained. The spectra of fungal samples showed significant differences interpreted in terms of biochemical composition using characteristic bands of proteins, polysaccharides, lipids, and triterpenoids. Obviously, for the transverse sections in trama, especially in the basal part, the most intense bands at 950-1200 cm-1 corresponded to polysaccharide vibrations, while for the superficial sections, the bands of carbonyl and aliphatic groups of triterpenoids at 1310-1470, 1550-1740, and 2850-2980 cm-1 predominated. The pilei, especially hymenium tubes, apparently contained more proteins than the bases and stipes, as evidenced by the intense bands of amide vibrations at 1648 and 1545-1550 cm-1. The specificity of the Ganoderma basidiocarp is a densely pigmented surface layer rich in triterpenoids, as proved by ATR-FTIR spectroscopy. The spectral differences corresponding to the specificity of the triterpenoid composition may indicate the prospects of individual strains and species of this genus for cultivation and further use in food, cosmetics, or medicine.
Keywords: medicinal fungus Ganoderma; ATR-FTIR spectroscopy; triterpenoids; biochemical composition; basidiocarp